Genome-wide methylation analysis of DNMT3B gene isoforms revealed specific methylation profiles in breast cell lines. (September 2016) - Plourde, Karine V; Labrie, Yvan; Ouellette, Geneviève; Pouliot, Marie-Christine; Durocher, Francine
Aim: The goal of this study is to characterize the specific methylation profile triggered by DNMT3B protein isoforms expressed at different levels in breast cell lines.Materials & methods: Microarray DNA methylation data were analyzed and associated with functional genome annotation data.Results: A large spectrum of DNMT3B3/DNMT3B2 expression ratio values was observed in parental breast cell lines. According to their methylation profiles, hierarchical clustering of untransfected cell lines revealed clustering based on their ER/PR status. Overexpression of DNMT3B3 triggered methylation changes of thousands of CpG sites in breast cells. Based on the trend of methylation changes, the results suggest an antiproliferative action of the DNMT3B3 isoform through a dominant negative effect on its wild-type counterpart DNMT3B2 .Conclusion: This study revealed specific pathways modulated by DNMT3B isoforms, which could regulate cell proliferation and other biological mechanisms. This illustrates the importance of multiple interactions between isoforms in the complexity of methylation processes.